Continuous hydroxyalkylation of p-Cresol to 2,2 `-methylenebis(4-Methylphenol) in a fixed bed reactor - Garade, Ajit C.; Hengne, Amol M.; Deshpande, Tushar N.; Shaligram, Sayali V.; Shirai, Masayuki; Rode, Chandrashekhar V. (Journal of Chemical Engineering of Japan, 2009)
{Catalytic activity of various solid acid catalysts is evaluated for the continuous hydroxyalkylation of p-cresol to [

Polybenzimidazole-based polymeric ionic liquids (PILs): effects of `substitution asymmetry' on CO2 permeation properties - Shaligram, Sayali V.; Wadgaonkar, Prakash P.; Kharul, Ulhas K. (Journal of Membrane Science, 2015)
Polymeric Ionic Liquids (PILs) are being considered as promising membrane materials for CO2 separation. Present work aims at investigating effects substitution asymmetry on imidazole moiety of two structurally different polybenzimidazoles (PBI-BuI and PBI-HFA) on physical, gas sorption and transport properties of the resulting film forming PILs possessing symmetric substitution, while keeping one of the N-substituent as methyl group. PILs were obtained with high degree of substitution. The halide anion of these PILs was exchanged with BF4-, Tf-2(N) over bar and HF (B) over bar anions. Effects of substituents, cationic backbone and type of anions on gas permeation properties of PILs using pure gases (He, H-2, N-2 and CO2) were examined at 20 atm upstream pressure and correlated with their physical properties. Combination of typical ionic liquid character (effective towards enhancing CO2 sorption) and looser chain packing (ease in gas diffusion) offered improved CO2 permeation characteristics. As an outcome, some of the PILs exhibited higher CO2 permeation than that of hydrogen, typically known as `reverse selectivity'. These asymmetrically substituted PILs enhanced not only the gas permeability, but also selectivity than their symmetrically substituted counterparts. (C) 2015 Elsevier B.V. All rights reserved.

Incorporation of rigid polyaromatic groups in polybenzimidazole-based polymeric ionic liquids: assertive effects on gas permeation properties - Shaligram, Sayali V.; Rewar, Anita S.; Wadgaonkar, Prakash P.; Kharul, Ulhas K. (Polymer, 2016)
Polymeric ionic liquids (PILs) have emerged as promising membrane materials for CO2 separation. The present work is aimed at investigating the effects of incorporation of rigid polyaromatic hydrocarbons, viz., pyrene and anthracene, in polybenzimidazole-based PILs. The effects of substituent and anion variation on the gas permeation properties of PILs using pure gases were examined at 20 atm upstream pressure. The results were correlated with physical properties of PILs. The pyrene substituted PIL exhibited similar to 10 fold increase in CO2 permeability as compared to its precursor polymer PBI-BuI. The combination of a CO2 specific anion and bulky group substitution offered higher CO2 permeability as well as appreciable permselectivity than their structural analogue that was devoid of IL functionality. The permeation properties of present PILs were superior to those of conventional glassy polymers such as polysulfone, matrimid and polycarbonate which are widely studied for their gas permeation properties. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Gas permeation; membranes; Polymeric ionic liquids

Polybenzimidazole based polymeric ionic liquids possessing partial ionic character: effects of anion exchange on their gas permeation properties - Rewar, Anita S.; Shaligram, Sayali V.; Kharul, Ulhas K. (Journal of Membrane Science, 2016)
Polymeric ionic liquids (PILs) are emerging as promising membrane materials for CO2 separation. Present work is in continuation with our earlier efforts on evaluating gas permeation properties (especially, CO2) of film forming PILs based on polybenzimidazoles and efforts towards improving their permeability by structural tuning. This work specifically aims at evaluating effect of anion variation in chosen PILs possessing partial N-quaternization of imidazole moiety of PBI-Bul. Three anions (viz., Tf2N-, BF4- and Ac-) were chosen for the bromide exchange of two PILs, viz., [TBzPBI-Bul][Br](10) and [TBzPBI-Bul][Br](18), possessing degree of PEI N-quaternization (DQ) as 10 and 18%, respectively. Concurrent effects of variation in anion and DQ were analyzed in terms of physical and gas permeation properties of the resulting PILs. All of them possessed amorphous nature, adequate thermal stability ( >= 250 degrees C) and solvent solubility, which are primary requisites towards their applicability as a membrane material. PILs possessing BF4- anion exhibited improved CO2 permeability coefficient as well as its permselectivity over CH4 and N-2, in comparison to their counterparts with other anions. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Anion exchange; Gas separation; Polybenzimidazole; Polymeric ionic liquids (PILs)

Synthesis and properties of poly(arylene ether)s based on 3-pentadecyl 4,4'-biphenol - Tawade, Bhausaheb V.; Shaligram, Sayali V.; Valsange, Nitin G.; Kharul, Ulhas K.; Wadgaonkar, Prakash P. (Polymer International, 2016)
A new biphenol, 3-pentadecyl 4,4-biphenol, was synthesized starting from 3-pentadecylphenol and was polycondensed with 4,4-difluorobenzophenone, 1,3-bis(4-fluorobenzoyl)benzene and bis(4-fluorophenyl)sulfone to obtain poly(arylene ether)s with biphenylene linkages in the backbone and pendent pentadecyl chains. Inherent viscosities and number-average molecular weights (M-n) of the poly(arylene ether)s were in the range 0.50 - 0.81 dL g(-1) and 2.2 x 10(4) - 8.3 x 10(4), respectively. Detailed NMR spectroscopic studies of the poly(arylene ether)s indicated the presence of constitutional isomerism which existed because of the non-symmetrical structure of 3-pentadecyl 4,4-biphenol. The poly(arylene ether)s readily dissolved in common organic solvents such as dichloromethane, chloroform and tetrahydrofuran and could be cast into tough, transparent and flexible films from their chloroform solutions. The poly(arylene ether)s exhibited T-g values in the range 35-60 degrees C which are lower than that of reference poly(arylene ether)s without pentadecyl chains. The 10% decomposition temperatures (T-10) of the poly(arylene ether)s were in the range 410-455 degrees C indicating their good thermal stability. A gas permeation study of poly(ether sulfone) containing pendent pentadecyl chains revealed a moderate increase in permeability for helium, hydrogen and oxygen. However, there was a large increase in permeability for carbon dioxide which could be attributed to the internal plasticization effect of pendent pentadecyl chains. (c) 2016 Society of Chemical Industry
Keywords: cashew nut shell liquid (CNSL); gas permeation study; pentadecyl; poly(arylene ether)s; thermal stability

Synthesis, characterization, and gas permeation properties of adamantane-containing polymers of intrinsic microporosity - Shrimant, Bharat; Shaligram, Sayali V.; Kharul, Ulhas K.; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2018)
A new bis(catechol) monomer, namely, 4,4-((1r,3r)-adamantane-2,2-diyl)bis(benzene-1,2diol) (THADM) was synthesized by condensation of 2-adamantanone with veratrole followed by demethylation of the formed (1r,3r)-2,2-bis(3,4 dimethoxyphenyl)adamantane. Polycondensation of THADM and various compositions of THADM and 5,5,6,6-tetrahydroxy-3,3,3,3-tetramethylspirobisindane was performed with 2,3,5,6-tetrafluoroterephthalonitrile (TFTPN) to obtain the homopolymer and copolymers. These polymers demonstrated good solubility in common organic solvents such as dichloromethane, chloroform, and tetrahydrofuran and could be cast into tough films from their chloroform solutions. GPC analysis revealed that number average molecular weights of polymers were in the range 48,100-61,700 gmol(-1), suggesting the formation of reasonably high molecular weight polymers. They possessed intrinsic microporosity with Brunauer-Emmett-Teller (BET) surface area in the range 703-741 m(2)g(-1). Thermogravimetric analysis of polymers indicated that 10% weight loss temperature was in the range 513-518 degrees C demonstrating their excellent thermal stability. THADM-based polymer of intrinsic microporosity (PIM) showed P(CO2)=1080, P(O-2)=232 and appreciable selectivity [(CO2/CH4)=22.6, (CO2/N-2)=26.7, and (O-2/N-2)= 5.7]. The gas permeability measurements revealed that with increase in the content of adamantane units in PIMs, selectivity increased and permeability decreased, following the trade-off relationship. The gas separation properties of PIMs containing adamantane units were located close to 2008 Robeson upper bound for gas pairs such as CO2/CH4, CO2/N-2, H-2/N-2, and O-2/N-2. (c) 2017 Wiley Periodicals, Inc.
Keywords: adamantane; Gas permeation; intrinsic microporosity; membranes; structure-property relations